2006
DOI: 10.1038/ng1915
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and functional evolution of the Drosophila melanogaster sperm proteome

Abstract: In addition to delivering a haploid genome to the egg, sperm have additional critical functions, including egg activation, origination of the zygote centrosome and delivery of paternal factors. Despite this, existing knowledge of the molecular basis of sperm form and function is limited. We used whole-sperm mass spectrometry to identify 381 proteins of the Drosophila melanogaster sperm proteome (DmSP). This approach identified mitochondrial, metabolic and cytoskeletal proteins, in addition to several new funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
310
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(339 citation statements)
references
References 27 publications
27
310
1
1
Order By: Relevance
“…First, at least four of them are expressed at the mRNA level and collectively account for one-fifth of the functional Mst77F-like mRNA. The Mst77Y mRNAs most likely are translated, since they are similar to the Mst77F mRNA; unfortunately none of these proteins (Mst77F or Mst77Y) were detected in the D. melanogaster sperm proteome (Dorus et al 2006) or in the whole male reproductive system (Takemori and Yamamoto 2009), so we cannot prove (or disprove) the expression of the Mst77Y genes at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…First, at least four of them are expressed at the mRNA level and collectively account for one-fifth of the functional Mst77F-like mRNA. The Mst77Y mRNAs most likely are translated, since they are similar to the Mst77F mRNA; unfortunately none of these proteins (Mst77F or Mst77Y) were detected in the D. melanogaster sperm proteome (Dorus et al 2006) or in the whole male reproductive system (Takemori and Yamamoto 2009), so we cannot prove (or disprove) the expression of the Mst77Y genes at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…The recently reported D. melanogaster sperm proteome has revealed that there has been a significant proportion of duplications among sperm protein genes (Dorus et al 2006), which could fuel rapid evolution across species. However, in comparisons between D. melanogaster and D. simulans, Dorus et al (2006) found that more than half of the sperm proteome genes had d N values ,0.01, suggesting that selection is constraining the evolution of structurally and functionally important genes.…”
Section: Discussionmentioning
confidence: 99%
“…One intriguing possibility is that AgOrs act to mediate spermatozoa responses to endogenous signaling molecules. Indeed, several studies have suggested the existence of signaling pathways in insect sperm, including proteomics analyses in Aedes aegypti (18) and Drosophila melanogaster (19), although ORs were not identified in those studies. Importantly, OR expression in male germ cells has been reported for numerous mammalian species (20)(21)(22) and evidence for functional expression of ORs in human and mouse sperm have been described (23)(24)(25)(26)(27), although the requirement for human ORs in ligand recognition and fertilization has been seriously challenged (28).…”
mentioning
confidence: 99%